Small bowel obstruction due to phytobezoar and adhesions following laparoscopic cholecystectomy - Abu jkeim, Nidal; Al hazmi, Ahmad; Alawad, Awad; Ibrahim, Rashid; Abu damis, Ahmad; Tawfik, Samir; Mansour, Mohammed (International Journal of Medicine, 2015)
We report a case of 51 –year-old female with history of laparoscopic cholecystectomy presented with abdominal pain and diagnosed as small bowel obstruction caused by adhesions. The initial presentation was periumbilical pain with nausea and vomiting. Plain abdominal radiograph showed dilated small bowel loops and multiple air fluid levels. Due to failure of conservative treatment, laparotomy was performed. An open metallic clip was adhering the bowel to the gallbladder fossa causing sharp angulation. A phytobezoar proximal to this angulation was exteriorized through enterotomy. The patient was recovered smoothly and discharged from our hospital.